Comparison between Protective Effects of Resveratrol and Atorvastatin against Atherogenic Dyslipidemia in Rats - Mehdi Kian; Maryam Ranjbar-Zahedani; Mehdi Bonyani; Hadis Asadimehr; Mehran Nouri; Mohammad Bakhtiari; Sasan Amanat (International Journal of Nutrition Sciences, 2023)
Background: Dyslipidemia puts patients at risk of cardiovascular diseases, which are the most cause of premature deaths worldwide. This study determined protective effects of resveratrol (RVL) and atorvastatin (ATV) in rats fed with a high-fat/high-fructose (HFHF) diet were compared for e treatment of atherogenic dyslipidemia.Methods: Thirty-six adult male Sprague Dawley rats were divided into 4 groups, including a group fed with a standard diet and three groups fed with a HFHF diet for 12 weeks. In two groups, in addition to HFHF diet, animals received RVL (100 mg/kg) and ATV (10 mg/kg) by gavage. After 12 weeks, levels of body and heart weights, systolic blood pressure(SBP), serum biomarkers of atherogenic dyslipidemia, insulin resistance, and malondialdehyde (MDA) in the heart tissue were measured.Results: Rats received the HFHF diet showed an elevation (p<0.05) in body and heart weight, SBP, serum total triglycerides (T-TGs), total cholesterol (T-CHOL), low-density lipoprotein CHOL (LDL-C), insulin resistance, aspartate aminotransferase (AST), and tumor necrosis factor- alpha (TNF-α), and also, elevated MDA content in the heart tissue. The administration of RVL significantly reduced (p<0.05) heart weight, SBP, serum T-TGs levels, insulin resistance, TNF-α, and cardiac MDA in rats received HFHF diet. On the other hand, the administration of ATV significantly decreased (p<0.05) heart-weight, and serum levels of T-TGs, T-CHOL, LDL-C, and TNF-α.Conclusion: RVL at a dose of 10 mg/kg was not a better protective medication against atherogenic dyslipidemia; but it may be applicable as a complementary medication with ATV.